2001
DOI: 10.1002/app.1260
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of bipolar membranes (I)

Abstract: ABSTRACT:The bipolar membranes were prepared by charged material of polysulfone as a base. The bipolar membranes were composed of a solvent-resistant anion exchange layer with a crosslinking matrix prepared by the reaction of chloromethylated polysulfone in DMF with diamine, an interfacial layer made from chloromethylated polysulfone solution in DMF containing cation exchange resin and amine, and a cation exchange layer made from sulfonated polysulfone dispersing cation resin powder. The prepared bipolar membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…Therefore, the most crucial aspect of these applications is the bipolar membrane itself. For preparing such membranes, various methods has been initiated, such as preparing directly from commercial cation and anion exchange membranes by adhering with heat and pressure or with an adhesive paste [145], preparing by casting a cation exchange polyelectrolyte solution (or an anion exchange polyelectrolyte solution) on a commercial anion exchange membrane (or on a cation exchange membrane) respectively [146,147], or preparing from the same base membrane by simultaneous functionalizing at the two membrane sides [148][149][150][151] or selectively functionalizing on one side to give cation selectivity and on the other side to give anion selectivity, etc. [152].…”
Section: Bipolar Ion Exchange Membranesmentioning
confidence: 99%
“…Therefore, the most crucial aspect of these applications is the bipolar membrane itself. For preparing such membranes, various methods has been initiated, such as preparing directly from commercial cation and anion exchange membranes by adhering with heat and pressure or with an adhesive paste [145], preparing by casting a cation exchange polyelectrolyte solution (or an anion exchange polyelectrolyte solution) on a commercial anion exchange membrane (or on a cation exchange membrane) respectively [146,147], or preparing from the same base membrane by simultaneous functionalizing at the two membrane sides [148][149][150][151] or selectively functionalizing on one side to give cation selectivity and on the other side to give anion selectivity, etc. [152].…”
Section: Bipolar Ion Exchange Membranesmentioning
confidence: 99%
“…In general, a good membrane is one with low energy consumption, high current efficiency, high product purity, and good long-term stability [7]. The energy required by a commercially available BPM to produce hydroxide ions and protons should correspond very closely to the theoretical potential drop.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more and more attention has been paid to modification of cation layer or anion layer, and introduction of catalytic interlayer to promote water splitting. 11 Simons found that water splitting of a BPM was promoted when the cation or anion layer was coated with one or more suitable inorganic electrolyte such as sodium metasilicate, chromic nitrate, ruthenium trichloride, or indium sulfate. 12 Xu et al prepared the anion layers with different ammonium groups by reacting the bromomethylated poly(2,6-dimethyl-1,4-phenylene oxide) (BPPO) with different amines, and then the corresponding BPMs were prepared by casting the sulfonated poly(phenylene oxide) (PPO) solution on these anion exchange layers.…”
Section: Introductionmentioning
confidence: 99%